Insulin says NO to cardiovascular disease - Qiujun Yu; Feng Gao; X. L. (2010)
It is well recognized that insulin resistance found in patients with type 2 diabetes and obesity is a major risk factor for cardiovascular disease. Since its discovery in the 1920s, insulin has been used as an essential therapeutic agent in diabetes for blood glucose management. Recent studies demonstrate that insulin signalling is essential for normal cardiovascular function, and lack of it (i.e. insulin resistance) will result in cardiovascular dysfunction and disease. Moreover, insulin is the key component of glucose–insulin–potassium cocktail and exerts significant cardiovascular protective effect via a phosphatidylinositol 3′-kinase–protein kinase B–endothelial nitric oxide synthase (PI3K-Akt-eNOS)-dependent signalling mechanism in addition to its metabolic modulation, which renders it a potent organ protector in multiple clinical applications. This review focuses on insulin-initiated PI3K-Akt-eNOS survival signalling, with nitric oxide as an 'end effector' delivering cardioprotection in health and disease (especially in ischaemic heart disease), and highlights the impairment of this survival signalling as a key link between insulin resistance and cardiovascular disease.